THE DEVELOPMENT AND APPLICATION OF TONGUE DIAGNOSIS CABIN - Ma, Yu- Hui; Li, Lin- Feng; Zhang, Yu- Xuan; Zhang, Yu; Wang, Yu- Ting; Han, Si- Yuan; Liang, Yu- Rong (Journal of Biomedical and Pharmaceutical Research, 2019)
On the basis of a large number of previous studies, we develop the TCM Tongue diagnosis mobile phone software based on artificial intelligence technology which is named Tongue Diagnosis Cabin. The software utilizes and improves the digital objectification technology of modern tongue image to overcome the influence of the pixel limitation of the mobile phone, the complex shooting environment, the unstable light source and other conditions on the color and definition of the original tongue image, and reduces the total difference between the remote tongue image and the original tongue image color, so as to achieve clinical visual equivalence. The software is based on the mobile phone, which is easy to operate with intelligently guidance and superior performance, and can promote the development of digitalization and telemedicine of tongue diagnosis. Keywords: tongue diagnosis cabin; tongue diagnosis; intelligence; mobile; telemedicine